Toxic effects of cadmium microparticles on the respiratory system. An experimental study on rats and mice. - Bouley, Georges; Dubreuil, Alain; Despaux, Nicole; Boudene, Claude (Scandinavian Journal of Work, Environment & Health, 1977)
An experimental study on rats and mice. Scand. j. work environ. & health 3 (1977) 116--121. Experiments on male, specific pathogen-free rats (193) and mice (66) are reported. The test and control animals received a single 15-min exposure to cadmium (cadmium oxide) and aluminum (alumina) microparticles, respectively. The air cadmium content was 10 mg/m3, and 4 microgram of this metal was retained by the lungs of the rats. The animals were observed for 24 days. The following significant differences appeared between the control and test groups: in the cadmium exposed rats the relative lung weight (percentage of body weight) became temporarily higher; the absolute number of alveolar macrophages decreased at first and then increased; numerous polymorphonuclear and lymphocytic cells appeared in the alveoli. According to these inflammatory phenomena, at the 48th h after exposure, there was an alteration in the clearance kinetics of inhaled bacteria and an increase in the death rate of cadmium exposed animals following a test infection with Salmonella enteritidis (rats) or Pasteurella multocida (mice) aerosols. The mechanism of cadmium toxic action on the respiratory system is discussed.
Keywords: air pollution; airborne infection; cadmium; cadmium microparticle; experimental study; mice; microparticle; mouse; rat; respiratory system; toxic effect